(untitled) (Marketing Journal, 2025)
This article analyzes the issues of organizing production in the building materials industry on the principles of quality management. Despite the growth in production volumes observed in recent years in the industry, there have been a number of systemic problems regarding product quality, compliance with standards, international competitiveness and ensuring export potential. In particular, the volume of production of cement, ceramic tile, construction glass and other materials, their quality indicators and factors affecting production processes were studied in depth. As a result of the work, the main problems such as obstacles to the introduction of quality management into practical activities — old technologies, low personnel qualifications, inefficiency of standardization and certification — were systematized.